Cyclicality of real wages in the USA and Germany: New insights from wavelet analysis - Martyna Marczak; Víctor Gómez (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
This article provides new insights into the cyclical behavior of consumer and producer real wages in the USA and Germany. We apply two methods for the estimation of the cyclical components from the data: the approach based on the structural time series models and the ARIMA-model-based approach combined with the canonical decomposition and a band-pass filter. We examine the extracted cycles drawing on two wavelet concepts: wavelet coherence and wavelet phase angle. In contrast to the analysis in the time or frequency domains, wavelet analysis allows for the identification of possible changes in cyclical patterns over time. From the findings of our study, we can infer that the USA and Germany differ with respect to the lead-lag relationship of real wages and the business cycle. In the USA, both real wages are leading the business cycle in the entire time interval. The German consumer real wage is, on the other hand, lagging the business cycle. For the German producer real wage, the lead-lag pattern changes over time. We also find that real wages in the USA as well in Germany are procyclical or acyclical until 1980 and countercyclical thereafter.
urn:nbn:de:bsz:100-opus-7267
Keywords: E32; C22; C32; J30; 330; real wages; business cycle; wavelet analysis; wavelet phase angle; trend-cycle decomposition; structural time series model; ARIMA-model-based approach; band-pass filter; Reallohn; Konjunktur; Zustandsraummodell; Zeitreihenanalyse; Schätzung; Deutschland; USA